PEMIKIRAN K.H. BADARUDDIN TENTANG PEMBAHARUAN PENDIDIKAN DI PONDOK PESANTREN DARUSSALAM MARTAPURA - Salam, Abdul (Pascasarjana UIN ANTASARI Banjarmasin, 2009)
This paper explores the renewing idea of K. H. Badruddin during his leading period in Pondok Pesantren Darussalam, Martapura. Here, he made some changes in education system, curriculum, and facilities of study. In curriculum aspect, he developed four kinds of educational curriculum those are: (1) the old pondok curriculum for religion (Diniyah) school; (2) the SKB three minister curriculum for the degree of Ibtidaiyah till the high college Darussalam with giving the official passing certificate; (3) the national education department curriculum for SMP and STM/SPK Darussalam; and (4) the agriculture education department curriculum for SPP/SPMA Darussalam. Also in his period, the rebuilding of syariah faculty become STIS Darussalam.